Simultaneous Bilateral Total Knee Arthroplasty in Elderly: Are There Factors that Can Influence Safety and Clinical Outcome? - G. Piovan; D. Screpis; S. Natali; V. Iacono; M. Baldini; L. Farinelli; M. Guerriero; C. Zorzi (Advances in Orthopedics)
Objective. The aim of this study was to look for preoperative patients’ related factors correlating with worse clinical outcomes in a cohort of elderly patients undergoing simultaneous bilateral total knee arthroplasty (SiBTKA) to search for risk factors, which may influence clinical outcomes and safety. Subjects and Methods. The hospital database was mined searching for patients older than 70 years that underwent SiBTKA for severe bilateral knee osteoarthritis (OA) between 2012 and 2016. Preoperative clinical information, Oxford Knee Score (OKS), and Knee Injury and Osteoarthritis Outcome Score (KOOS) prior to surgery were recorded. The OKS and the KOOS were submitted again after a minimum of 5 years of follow-up (FU). Results. An improvement was observed in all clinical scores at last FU. The major complication rate was 5.4%. No patients’ clinical data showed correlation with perioperative complications or need for transfusions. Functional scores at the last FU were negatively affected by age at surgery and positively affected by preoperative clinical scores. Discussion. In the setting of severe symptomatic bilateral knee OA, SiBTKA seems to be effective in improving symptoms at midterm follow-up, with acceptable rates of perioperative complications in patients older than 70. Higher age at surgery and lower preoperative functional scores are associated with worse clinical outcomes at FU. This could assist surgeons in advising patients that delay of surgical treatment could worsen outcomes.